2017
DOI: 10.1007/s13760-017-0852-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thickness of retinal nerve fiber layer, ganglion cell layer, and choroidal thickness in essential tremor: can eyes be a clue for neurodegeneration?

Abstract: The pathology of essential tremor (ET) and underlying mechanisms of the disease are still unclear, but an increasing amount of research has been conducted on the subject. Discussions are ongoing about ET's definition as a neurodegenerative disease. Optic coherence tomography (OCT) provides a window to the brain where direct visualization of central nervous system (CNS) changes may be possible, and it can help us to develop a new point of view on ET. The goal of this study was to examine OCT parameters in ET. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…A popular disease model, initially proposed in the 1970s [138], attempted to link ET to an abnormal inferior olivary nucleus; however, empiric support for that model is limited [57,139,140] and the model has recently fallen out of favor [55,56]. More recent research in the field has focused on the cerebellum, where there has been a reconceptualization of the disease as one of cerebellar degeneration, as will be discussed below [29,35,[37][38][39][40][41][42][43][44][45][46][47].…”
Section: Pathologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A popular disease model, initially proposed in the 1970s [138], attempted to link ET to an abnormal inferior olivary nucleus; however, empiric support for that model is limited [57,139,140] and the model has recently fallen out of favor [55,56]. More recent research in the field has focused on the cerebellum, where there has been a reconceptualization of the disease as one of cerebellar degeneration, as will be discussed below [29,35,[37][38][39][40][41][42][43][44][45][46][47].…”
Section: Pathologicalmentioning
confidence: 99%
“…The pathophysiology is of ET unclear, and is likely heterogeneous. Recent work has recast it as one that is often due to cerebellar and cerebellar pathway dysfunction [28][29][30][31][32][33][34][35][36] as well as one that is likely degenerative [29,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are very few researches on visual functions in ET, and color vision abnormalities have not been detected [16,17]. The studies determining RNFL thickness with OCT in ET had different results [18][19][20]. However, we did not find any study comparing RNFL thickness in both PD and ET patients.…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, we also found similar decreases in RNFL thickness in the ET group. We found few studies in the literature where RNFL of ET patients was assessed by OCT [18][19][20]. One of these studies was a pilot study with a small number of patients where it was found that foveal thickness decreased in ET patients compared to the controls, but this difference was not statistically significant [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation